Relationship between Innovation and Competitiveness in the Non-financial Ventures of the Popular and Solidarity Economy - Maya Carrillo, Maribel (2022)
Current business dynamics require ventures to implement innovation processes to generate value for customers, gain competitiveness, and be sustainable in the market. This study analyzes the activities, capacities, and results of innovation and the relationship with the competitiveness factors of ventures in the popular and solidary non-financial sector, in order to understand the current reality and the basis for future decision-making with an influence in business growth. This research is non-experimental, using a quantitative and correlational approach by conducting surveys to the presidents of 68 venturesin the Canton Quito between the months of March and June 2020. The results showed a predominant medium level of innovation and competitiveness, with organizational learning standing out in the capacity for innovation. In terms of technological innovation, improvements in the quality of products and new production methods can be identified; as for non-technological innovation, new communication and marketing channels and new business practices have been implemented. With regard to competitiveness, the ventures are focused on human resources and marketing. There is a strong positive correlation between innovation and competitiveness.